Respuesta :
Answer:
[tex]y=(x+3)^{2} -1[/tex]
Step-by-step explanation:
General equation of a parabola that opens up is [tex]y=a(x-h)^{2} +k[/tex] , a>0
So equation becomes [tex]y=(x-h)^{2} +k[/tex] which implies option A and option B can never be true for this parabola.
Also this parabola's vertex lies in 3rd quadrant where coordinates of both x and y will be negative.
So, the equation of parabola will be of the form [tex]y=(x+h)^{2} - k[/tex]
Hence, option 4 that is [tex]y=(x+3)^{2} -1[/tex] is correct.